Purification of a thermostable DNA polymerase from Thermus thermophilus HB8, useful in the polymerase chain reaction - Carballeira, N (BioTechniques, 1990)
A thermostable DNA polymerase, isolated from the thermophilic strain Thermus thermophilus HB 8 was purified by a five-step procedure which provides a high yield and a homogeneous preparation. The molecular weight was estimated to be 67,000 daltons and the extension rate was determined to be 1500 nucleotides per minute. The enzyme works in polymerase chain reaction conditions similar to those used for Taq polymerase from Thermus aquaticus